Inovasi Produk pada Akad Mudharabah di Bank Syariah Indonesia (BSI) - Naswa Sasmita; Rizky Bayu Pratama; Natasya Natasya; Husni Kamal (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
This study examines the innovation of Hajj Savings products based on the mudharabah contract at Bank Syariah Indonesia (BSI). The innovations include digitalization of services, integration with the Ministry of Religious Affairs’ SISKOHAT system, and the development of new features such as collective savings, gamification, and auto-debit. The objective of these innovations is to facilitate Muslims in planning and saving for Hajj funds according to Sharia principles, enhance service accessibility, and provide added value tailored to modern customer needs. The findings indicate that these product innovations offer significant benefits to customers, including convenience, security, and fair profit-sharing, as well as advantages for BSI in terms of increased third-party funds, operational efficiency, and market expansion. This study emphasizes the importance of sustainable innovation grounded in Sharia principles in the development of Islamic banking products to support financial inclusion and improve service quality.